Slidesgo Assisted Interactive Media Development to Enhance Motivation in Technology Learning for Fifth Grade Students in Elementary school - Nuriyah Salsyabila; Zulherman Zulherman (Universitas Labuhanbatu, 2025)
Background: The lack of motivation to learn of students can make the learning process in grade V of elementary school hampered. Low motivation to learn can be seen from the lack of enthusiasm from students and quickly feeling bored when learning in class and the learning media used by teachers are considered uninteresting or monotonous. Methodology: The method used in this study is Research and Development (RnD) with the ADDIE (Analyse, Design, Development, Implementational, Evaluation) model. This research was conducted at 3 elementary school such as SDN Balimester 01 AM, SDN Balimester 06 AM and SDN Rawa Bunga 11 AM. Results: The results of the assessment obtained from the Expert Lecturers include: 1) Media experts give a validation assessment of 72 % or